Plastid phylogenomic insights into the evolution of Caryophyllales - Yao, Gang; Jin, Jian-Jun; Li, Hong-Tao; Yang, Jun-Bo; Mandala, Venkata Shiva; Croley, Matthew; Mostow, Rebecca; Douglas, Norman A.; Chase, Mark W.; Christenhusz, Maarten J.M.; Soltis, Douglas E.; Soltis, Pamela S.; et al. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Plastomes of 95 species (80 genera) within Caryophyllales were newly sequenced.•The deep-level relationships of Caryophyllales were resolved.•A fossil-calibrated chronogram with Caryophyllales-wide sampling is provided.•A rapid radiation of Caryophyllales in the mid-Cretaceous was detected.•Relationship between plastome structure and molecular evolution was discussed. The Caryophyllales includes 40 families and 12,500 species, representing a large and diverse clade of angiosperms. Collectively, members of the clade grow on all continents and in all terrestrial biomes and often occupy extreme habitats (e.g., xeric, salty). The order is characterized by many taxa with unusual adaptations including carnivory, halophytism, and multiple origins of C4 photosynthesis. However, deep phylogenetic relationships within the order have long been problematic due to putative rapid divergence. To resolve the deep-level relationships of Caryophyllales, we performed phylogenomic analyses of all 40 families of Caryophyllales. We time-calibrated the molecular phylogeny of this clade, and evaluated putative correlations among plastid structural changes and rates of molecular substitution. We recovered a well-resolved and well-supported phylogeny of the Caryophyllales that was largely congruent with previous estimates of this order. Our results provide improved support for the phylogenetic position of several key families within this clade. The crown age of Caryophyllales was estimated at ca. 114.4 million years ago (Ma), with periods of rapid divergence in the mid-Cretaceous. A strong, positive correlation between nucleotide substitution rate and plastid structural changes was detected. Our study highlights the importance of broad taxon sampling in phylogenomic inference and provides a firm basis for future investigations of molecular, morphological, and ecophysiological evolution in Caryophyllales.